PRARANCANGAN PABRIK SELULOSA ASETAT DARI COTTON DAN ASETAT ANHIDRID DENGAN KAPASITAS 6.000 TON / TAHUN - , SYABILLA MUJAHIDAH; , Wiratni, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cellulose acetate is an ingredient that can be used as the manufacture of clothing and fabric at household purposes. It is also used as the material for the woven threads in the textile industry, as a filter on a cigarette, material for plastic sheets, films, and also paints. Manufacture of cotton from cellulose acetate and acetic anhydride takes place in several reaction stages. At first, cotton (cellulose) and acetic anhydride react to produce cellulose acetate and acetic acid in a batch stirred tank reactor with sulfuric acid as catalyst. This reaction takes place at temperature of 45Â° C and pressure of 1 atm. Next, reaction occurs in a hidroliser with temperature of 50Â° C and pressure of 1 atm, which is the addition of water are included in the form of acetic acid solution with a low concentration. The solution is added to stop the acetylation reaction and begin the process of hydrolysis. This is followed by the neutralization of sulfuric acid catalyst remaining in the mixture of primary cellulose acetate from acetylation unit using sodium acetate. Then, the purification step of cellulose acetate from the impurities and the drying of cellulose acetate flake are done. The plant is designed with a capacity of 6,000 tons/year. Products of cellulose acetate with a purity of 99% is produced from cotton as much as 3,375.5 tons/year and acetic anhydride as much as 7,087.61 tons/year. Utilities includes water as much as 202,151.58 tons/year